PEMBARUAN UNDANG-UNDANG PERADILAN TATA USAHA NEGARA PASCA-REFORMASI DI ERA PERADILAN ELEKTRONIK - Muhammad Adiguna Bimasakti (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2020)
In the past decade there has been a massive reform in the Indonesian judiciary system, especially regarding State Administrative Court. As from the enactment of Law No. 14 of 2008 concerning Openness of Public Information, until the enactment of Law No. 9 of 2018 concerning Non-Tax State Revenues opened a tap that expands the competence/authority of the State Administrative Court so that not only the authority to adjudicate disputes regarding that of individual-concrete administrative decision (beschikking) but also the authority to adjudicate all types of administrative decisions as long as they are not statutory regulations, and also to adjudicate disputes regarding administrative factual-deed. Morover, within the enactment of Supreme Court Regulation No. 1 of 2019 also opened a new paradigm about Electronic Litigation. This paper will discuss the urgency of renewing the State Administrative Court Law in terms of expanding absolute competence, the implementation of Electronic Litigation, and also about synchronization with other laws and regulations. The method used in this paper is library research that is research that takes resources from relevant literature. In this paper it can be concluded that it is deemed necessary to reform the substance in the obsolete State Administrative Court Law.